Positive Personality Education: An Ontological Aspect - Shevchenko, Halyna Pavlivna; Antonenko, Tetiana Leonardivna; Safonova, Iryna Oleksiivna (Journal of History Culture and Art Research, 2020)
The article highlights the problem of positive personality education in the ontological aspect. The authors believe that pedagogy, as a branch of human studies, requires a deep study of the multidimensionality and multivaluedness of a man, understanding his inwardness basing on a new methodology of discovering an integrated and holistic world. “The Man in the World and the World inside the Man” is a concept, which, in our opinion, should become the defining context of modern philosophy of education and pedagogical science, in particular. This concept has two sides. The first one, the Man in the World, testifies that a man is an integral part of the objective world. The other side, the World inside the Man, defines the inner dimension of man. The idea of positive education is based on the assumption that the pursuit of the best things such as values, meanings, ideals of the highest order, the ability to seek and create positive things in the world should become a need for a highly developed personality. For the realization of this idea, it is extremely important to form positive thinking among student youth. According to the authors, positive thinking is a reflection of the formation of a holistic picture of the world of a man, where stable systems of personal meanings and values are the defining basis. It is the values and meanings dominant that determines the nature of the relationship of a man to the world. According to the authors, the interest should be the agent for transmitting positive values and meanings. A special role in this process belongs to the art, because the art itself contributes to the development of the human in the man, brings a sense of fullness of life, and human happiness. We are convinced that only in this way it is possible to overcome the alienation of a man from life and to project the future prospects of his development and live a happy life.